2019
DOI: 10.1177/1049909119859844
|View full text |Cite
|
Sign up to set email alerts
|

Medical Assistance in Dying (MAiD): A Descriptive Study From a Canadian Tertiary Care Hospital

Abstract: Background: In June 2016, the Government of Canada passed Bill C-14 decriminalizing medically assisted death. Increasing numbers of Canadians are accessing medical assistance in dying (MAiD) each year, but there is limited information about this population. Objective: To describe the characteristic outcomes of MAiD requests in a cohort of patients at an academic tertiary care center in Toronto, Ontario, Canada. Methods: A retrospective chart review of patients making a formal request for a MAiD eligibility ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…8,9 Bravo et al found that over 70% of older adults, dementia caregivers, nurses, and physicians in Quebec agreed that it was acceptable to provide MAiD to an incompetent patient who was showing signs of distress and had requested MAiD in writing prior to losing capacity. 10 Studies by Nuhn et al 11 and by Selby et al 12 found that the primary reasons given by patients seeking MAiD were loss of function and loss of dignity, similar to our findings reported in Table 3. The Council of Canadian Academies (CCA) Expert Panel examining advance requests concurred with at least two of the policy conclusions emerging from this study: the need for clear definition of intolerable suffering by the patient; and having the requestor describe their motivations for choosing MAiD.…”
Section: Discussionsupporting
confidence: 90%
“…8,9 Bravo et al found that over 70% of older adults, dementia caregivers, nurses, and physicians in Quebec agreed that it was acceptable to provide MAiD to an incompetent patient who was showing signs of distress and had requested MAiD in writing prior to losing capacity. 10 Studies by Nuhn et al 11 and by Selby et al 12 found that the primary reasons given by patients seeking MAiD were loss of function and loss of dignity, similar to our findings reported in Table 3. The Council of Canadian Academies (CCA) Expert Panel examining advance requests concurred with at least two of the policy conclusions emerging from this study: the need for clear definition of intolerable suffering by the patient; and having the requestor describe their motivations for choosing MAiD.…”
Section: Discussionsupporting
confidence: 90%
“…Although the Can adian law itself is now under review, and the man datory reflection period may no longer be required in the updated legislation, identifying patients who are at high risk of a rapid change in condition remains clinically relevant. Previously published findings from both our group and others 12,20,21 have suggested that a request for MAiD is a reflec tion of the individual's longstanding personality characteristics, world view and lifelong values. Individuals accessing MAiD typ ically strongly desire control over the conditions of their endof life care and place importance on autonomy, independence and a sense of self.…”
Section: Discussionmentioning
confidence: 71%
“…11 Prior work has highlighted the importance that patients place on receiving MAiD once they have made the decision to proceed. [12][13][14] For those who are seriously ill or felt to be at risk of losing capacity to provide final consent, the 10day reflection period can be a source of marked anxiety for the patient, with providers needing to balance patientcentred care with adherence to the legislation. The reflection period can be waived if both assessors feel the patient is at immi nent risk of death or loss of capacity, but to date there are no evidencebased data to help assessors determine who might be at such risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We surveyed clinicians at a coffee shop inside a leading Canadian hospital that provided medical assistance in dying. 68 Each participant received one version (rich patient or poor patient) of the survey by randomised assignment ( online supplemental appendix §1 ). The typical participant was a middle-aged woman with professional training and years of medical experience (n=494).…”
Section: Resultsmentioning
confidence: 99%